International institutions : can interdependence work? - Keohane, Robert O. (1998)
Opines that international institutions are increasingly important, but they are not always successful. Notes that as the world moves toward new forms of global regulation and governance, the increasing impact of international institutions has raised new questions about how these institutions themselves are governed.